Harlem vs. Columbia University : Black student power in the late 1960s - Bradley, Stefan M. (University of Illinois Press, 2009)
In 1968-69, Columbia University became the site for a collision of American social movements. Black Power, student power, antiwar, New Left, and Civil Rights movements all clashed with local and state politics when an alliance of black students and residents of Harlem and Morningside Heights openly protested the school's ill-conceived plan to build a large, private gymnasium in the small green park that separates the elite university from Harlem. Railing against the university's expansion policy, protesters occupied administration buildings and met violent opposition from both fellow students and the police. In this dynamic book, Stefan M. Bradley describes the impact of Black Power ideology on the Students' Afro-American Society (SAS) at Columbia. While white students--led by Mark Rudd and Students for a Democratic Society (SDS)--sought to radicalize the student body and restructure the university, black students focused on stopping the construction of the gym in Morningside Park. Through separate, militant action, black students and the black community stood up to the power of an Ivy League institution and stopped it from trampling over its relatively poor and powerless neighbors. Bradley also compares the events at Columbia with similar events at Harvard, Cornell, Yale, and the University of Pennsylvania.
Keywords: Columbia University -- Student strike, 1968.; Columbia University; African American student movements -- New York (State) -- New York -- History.; Black power -- New York (State) -- New York -- History.; Morningside Park (New York, N.Y.) -- History.; Mouvements étudiants noirs américains -- New York (État) -- New York -- Histoire.; Black power -- New York (État) -- New York -- Histoire.; EDUCATION -- Higher.; SOCIAL SCIENCE -- Ethnic Studies -- African American Studies.; African American student movements; Black power; New York (State) -- New York; New York (State) -- New York -- Morningside Park; 1968; Electronic resource.; History